A Mapping The Sports Club Students in Bali (Department of Physical Education, Sport, Health and Recreation, 2017)
The aims of this research are (1) mapping of student sports clubs in Bali province based on sports achievement at elementary school student sports school, and (2) designing elementary school student sport concept in Bali province. The research method used survey method. Research approach with quantitative and qualitative combination approach. The results of the study were (1) mapping of students’ sporting achievements at Bali provincial / municipal elementary schools of various sports competed, (2) establishment of elementary school sports clubs to be undertaken by youth and sports education offices of Bali provincial / 3) the concept of a student sports club district / city in the province of Bali. The conclusions obtained were (1) the profile of the students’ sport achievement achieved by the elementary school students in the province of Bali, (2) the elementary school sports club was formed in accordance with the youth and sports education policy of the istrict / city in Bali province, (3) a student sports club district / city in the province of Bali.